Prognostic Value of Total Atrial Conduction Time Measured with Tissue Doppler Imaging to Predict the Maintenance of Sinus Rhythm after External Electrical Cardioversion of Persistent Atrial Fibrillation. Issue 3 (22nd July 2014) - Maffè, Stefano; Paffoni, Paola; Dellavesa, Pierfranco; Cucchi, Lorenzo; Zenone, Franco; Bergamasco, Luca; Paino, Anna Maria; Franchetti Pardo, Nicolò; Signorotti, Fabiana; Baduena, Lara; Parravicini, Umberto
<x xml:space="preserve">Abstract</x> Background Atrial fibrillation (AF) is the most common sustained arrhythmia, with a high recurrence rate, especially during the first months after cardioversion (CV). Few parameters have been evaluated as predictors for the maintenance of sinus rhythm (SR), with limited results. Recently total atrial conduction time (TACT) has been proposed as independent predictor of AF recurrence. The aim of this study was to investigate the prognostic value of TACT, measured using PA‐TDI duration, to predict 1‐year maintenance of restored SR after electrical CV. Methods and Results In a population of 104 patients (58 male, aged 70 ± 9) with persistent AF, submitted to external electrical CV, we performed a complete echocardiogram after restoring SR. The TACT was estimated by measuring the time delay between the onset of the P‐wave in lead II of the surface electrocardiogram and the peak A′‐wave on the tissue Doppler imaging (TDI) tracing of the left atrial lateral wall (so‐called PA‐TDI duration). After a mean follow‐up of 14 ± 2 months, 34 (33%) patients had recurrent AF, whereas 70 (67%) patients maintained SR. At multivariate analysis only PA‐TDI was identified as independent predictor of AF recurrence (HR 1.04; 95% CI 1.03–1.06; P < 0.001). Receiver operator characteristics curve analyses demonstrated a high degree of discrimination (area under the curve 0.923); with a cut point of 152 msec, we obtain a good diagnostic accuracy (sensitivity 91%, specificity 87%). Conclusion The TACT using TDI is an independent predictor of AF recurrence and can be used to predict the maintenance of SR after external electrical CV.